Immediate and delayed movement of resistant and susceptible adults of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) after short exposures to phosphine. Issue 6 (15th February 2023) - Morrison, William R; Brabec, Daniel; Bruce, Alexander; Arthur, Frank H; Athanassiou, Christos G
Abstract: BACKGROUND: During the last decade, the evaluation of certain behavioral attributes has been utilized as an indicator of resistance to phosphine. In this context, an underappreciated challenge may be the development of behavioral traits that are related with resistance to phosphine such as the movement to refugia and recovery of stored product insects after short exposures. Thus, the aim of the current study was to track the movement of phosphine‐resistant and ‐susceptible adults of the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), which is a major pest of stored products, after brief exposures to phosphine. Exposures were followed for extended intervals to assess the recovery patterns and how those patterns are related to known resistance to phosphine. A video‐tracking procedure coupled with Ethovision software was used to assess movement after exposure. RESULTS: Overall, we found baseline movement was less for phosphine‐resistant T. castaneum, suggesting resistance comes at a considerable fitness cost. In the presence of phosphine (1000 or 3000 ppm), there was a much greater reduction in movement for phosphine‐susceptible than phosphine‐resistant T. castaneum adults immediately after brief 5‐min exposures. Twenty‐four hours later, these effects were more variable and less apparent, regardless of the susceptibility level. CONCLUSIONS: The initial knockdown associated with successful fumigation may just be a temporary state whereafter insects shortly resume movement and may be able to seek out refugia from phosphine, thereby promoting the development of resistance. Our results strengthen a growing consensus that it is the speed to knockdown that truly matters, with quick knockdown indicating slow recovery and a reduced likelihood for the occurrence of resistance. © 2023 Society of Chemical Industry. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA. Abstract : The aim was to track the movement of phosphine‐resistant and ‐susceptible adults of Tribolium castaneum after brief exposures to phosphine. Exposures were followed for extended intervals to assess the recovery patterns, and we found in the presence of phosphine (1000 or 3000 ppm) there was a much greater reduction in movement for phosphine‐susceptible than phosphine‐resistant T. castaneum adults.